Proceedings of the First Workshop on Natural Language Interfaces - Awadallah, Ahmed; Su, Yu; Sun, Huan; Yih, Scott Wen-tau (Association for Computational Linguistics, 2020)
Natural language interfaces (NLIs) have been the "holy grail" of human-computer interaction and information search for decades. However, early attempts in building NLIs to databases did not achieve the expected success due to limitations in language understanding capability, extensibility and explainability, among others. The last 5 years have seen a major resurgence of NLIs in the form of virtual assistants, dialogue systems, and semantic parsing and question answering systems. The horizon of NLIs has also been significantly expanding beyond databases to, e.g., knowledge bases, robots, Internet of Things, Web service APIs, and more.